El Excentrico, 1963-06-05 - Garcia, Humberto:::Publisher:::::::::::: (San Jose, California; Garcia Printing, 2023)
June 05, 1963 [ 05 de junio de 1963]. Ano 13, No 16. Cover has a photographs of San Jose State College awards ceremony. The headline reads, "San Jose American G.I forum Scholarship recipients."